Modelación del crecimiento de Albizia niopoides (Mimosaceae) por métodos dendrocronológicos - Giraldo, Víctor David (2012)
Growth modeling of Albizia niopoides (Mimosaceae) using dendrochronological methods. The annual growth rings in tropical trees are fairly common, but their study is relatively recent. Growth rings were found in trees of Albizia niopoides from the Porce River Canyon, Central Cordillera of the Colombian Andes. A total of 33 cross-sections were collected from trees distributed throughout the study area from 664-870masl. Cross-dating, spaguetti plot and 14C analyses were used to demonstrate ring annuality, assuming as hypothesis that these are real annual growth rings. A combination of descriptive analysis of time series (smoothing and prewhitening) to filter climate noise and nonlinear regression with weighted residuals was used to fit the diameter to Korf´s growth model, in which the coefficient of determination reaches values close to 100%. The positive residual autocorrelation of order 1, although not significant, is explained by the existence of energy reserves in the stem and by the accumulation of diameter increments required for the construction of the diameter growth model. The current and mean annual maximum increment rates are 1.03 and 0.94cm/year at ages 18 and 46 years old, respectively. These trees are classified within the group of fast growing species which can reach a cut diameter of over 50cm in approximately 52 years.